Pelaksanaan Supervisi Akademik Melalui Pengelolaan Sarana dan Prasarana dalam Meningkatkan Kinerja Guru - Sucriah Sucriah (Jurnal Dedikasi Pendidikan, 2018)
To improve the performance of teachers, it is necessary to provide continuous and sustainable coaching. Improving teacher performance does not merely improve its competence either through upgrading, training and giving opportunities to develop more but also need to pay attention to the teachers from other aspect such as improvement of discipline, motivation, guidance or supervision, giving incentive, decent salary, thus allowing teachers to be satisfied in working as educators. This study aimed To determine the implementation of Academic Supervision Through Infrastructure Management in Improving Teacher Performance in Elementary School 68 Banda Aceh Lesson Year 2016/2017. Subjects in this study were all teachers in SD Negeri 68 Kota Banda Aceh, which were 10 people. Data collection techniques used in this study is the School Action Research consists of two cycles. Data analysis used in this research use quantitative descriptive statistic with percentage. The calculations in the data analysis shown the percentage of achievement which is further called with teacher performance improvement. The results showed that there was a significant increasing from cycle I to cycle II, where the number of scores achieved in cycle I of 250, increased to 380 in cycle II. The average value obtained by cycle I is 62.50%, increased to 95% in cycle II..